Governing middle-sized cities : (Lynne Rienner, 2000)
This collection of 12 case studies illustrates the range of problems facing mid-sized cities in the USA and the variety of approaches that mayors have used to cope with them. Topics covered include education, crime, economic development and the political incorporation of minorities.